Bibliometric and visual analysis of global research: Enhanced Recovery After Caesarean Surgery (ERACS) - Fithriani Sri Utami; Elsye Maria Rosa (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Background: ERACS (Enhanced Recovery after Caesarean Surgery) is a method developed in obstetric services. Its global popularity has grown in recent years. The purpose of this article is to find out the extent to which ERACS has been researched and published in the world over the past ten years. Researchers also want to know an overview of the scope of research related to ERACS. Methods: This research is a quantitative study by analyzing bibliographic data using the VOS viewer program. Bibliographic data on ERACS was searched through Scopus (www.scopus.com) and processed with the VOS viewer program. Results: 123 publications with ERACS-related papers over the previous 10 years were found in the search results. The most is in the United States. Nelson, G is the researcher who has the greatest productivity. In the analysis of terms in the research abstract, there are 5 clusters. The most widely used term in the article is “caesarean section” with 109 occurrences. Based on the keyword analysis used, cluster 1 theme is about "Postoperative care", cluster 2 theme is about "obstetric anesthesia", cluster 3 theme is about "preoperative and perioperative care", cluster 4 theme is about "postoperative pain" and cluster 5 theme is about "enhanced recovery after surgery". Conclusion: This bibliometric analysis presents the current state of ERACS programs from a variety of angles and serves as a resource and pointer for scholars conducting additional research. Postoperative care, obstetric anesthesia, preoperative and perioperative care, postoperative pain, and enhanced recovery after surgery are the themes that appear in this bibliometric analysis.